Life in politics : selected speeches and lectures, 1979-2004 - Sangma, P. A. (New Delhi, 2012)
Born in the remote West Garo Hills district of Meghalaya, P.A. Sangma rose to become the Speaker of the LokSabha in 1996, the first member of the Opposition to do so-surely a triumph of Indian democracy. A Life in Politics explores the political life of one of the most fascinating personalities on the Indian political scene. It traces his rise from a small tribal village to the highest echelons of the country's Parliament, profiling his contributions to Indian politics and development, as also his unrelenting fight for the protection of democratic institutions and the welfare of the common man. Almost every important speech that Sangma delivered in the LokSabha and the RajyaSabha has been incorporated here. Also included are his rulings as the Speaker, LokSabha, the speeches delivered by him at national and international conferences and seminars, and his midnight speech in the Central Hall of Parliament on the golden jubilee of India's Independence. These speeches reflect the vision and the concern of an eminent parliamentarian for the development of the country and its citizens, and give an insight into the working of the world's largest democracy. The book also contains messages by eminent politicians and personalities from other walks of life, including the prime minister, Union ministers, governors, chief ministers and trade union leaders, describing the multifaceted personality of Sangma. A Life in Politics is a tribute to a visionary leader and a useful guide to issues of prime importance to Indian democracy for young politicians, researchers and the common reader.
Keywords: "Sangma, Pumo Agitok - Autobiography"